Uncertainty Tolerance in Children with Attention-Deficit/Hyperactivity Disorder (ADHD) - Miliutina, Kateryna; Knyazev, Vladislav (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The study involved 45 children aged 7 to 9 years (mean age 7.9 years) diagnosed with ADHD, diagnosed by a psychoneurologist. Of our respondents there were 37 boys and 8 girls. All children attended secondary school, they did not have inclusive education. However, parents sought psychological help since they had impaired adaptation to school: behavioral disorders and lack of academic performance. A table of observation of emotional reactions and analysis of created stories was used to study children’s behavioral characteristics with ADHD. The task of compiling stories using five cubes (stimulus material – "Cubes of stories") was used as an independent variable. The observation table, created as a modification of the scale of differential emotions of Izzard, allowed to identify the specifics of children’s emotional reactions to different conditions of storytelling. This task was proposed to be performed in three different ways: 1) The child independently chooses cubes. 2) The cubes fall out accidentally, the glass with them shakes the child. 3) The cubes fall out accidentally; a glass with them shakes an adult. Children with ADHD are not a homogeneous group. In our study, they were divided into two subgroups, "risky" and "anxious". There is a high tolerance for uncertainty in the first of them, and in a situation of unpredictability and uncertainty, they are activated, emotionally uplifted, and some improvement in speech. In the second subgroup – a low level of tolerance for uncertainty, in these situations, children feel anxious, and if they think that they can somehow influence it, then guilt. In the "risky" group, children in a situation of uncertainty were dominated by interest, joy, and surprise. The children sometimes got angry and sad if the dice were "not good" and felt it would be challenging to write a story. The emotional spectrum in uncertainty in the anxiety group was different: fear, sadness, anger, and frustration. Disappointment and guilt arose in the children of this group when they threw the dice on their own. They considered themselves guilty of something unpleasant or difficult.